Severity of Lower Urinary Tract Symptoms among Middle Aged and Elderly Nigerian Men: Impact on Quality of Life - Patrick Temi Adegun; Philip Babatunde Adebayo; Peter Olufemi Areo (Advances in Urology)
Objectives. To compare the severity of LUTS among middle aged and elderly Nigerian men and determine the influence of LUTS severity on QoL. Methods. This cross-sectional study was conducted among new patients presenting with LUTS attending Urology clinic between 2011 and 2015. Assessment of symptoms was based on IPSS and bother score completed by the eligible subjects on the same day of their clinic visits. Results. Four hundred patients were studied comprising 229 middle aged and 171 elderly men. Interquartile range (IQR) of IPSS scores for men <65 years and those ≥65 years was 14.0 (16.0) and 19 (15.0), respectively (p<0.001). Mild LUTS was significantly associated with best, good, and poor quality of life while moderate LUTS was associated with poor QoL. Severe LUTS was significantly associated with all the categories of QoL (Best-Worst). Among the cohort of subjects with poor QoL, elderly patients had a significantly higher median IPSS score (p<0.05). Conclusions. There is no level of severity of LUTS in which patients’ QoL is not impaired although mild symptomatology may be associated with better QoL and severe symptomatology with poor QoL. Careful attention to QoL may help identify patients who require early and prompt treatment irrespective of the IPSS.